The Role of Heritage Connection in Consumer Valuation - Christensen, Katherine L.; Shu, Suzanne B. (Journal of Marketing Research, 2024)
Owners value heritage goods, items that connect them to a shared past, whether through their alma mater or their family history. This research considers the impact of heritage on owners who wish to sell such goods. In five studies, the authors demonstrate that sellers have a lower willingness to accept when selling heritage goods to buyers with a shared heritage connection relative to buyers without this connection (i.e., a heritage discount). This heritage discount cannot be explained by ingroup favoritism, sentimental value, or appropriateness of buyer usage and persists even when sellers perceive that the buyer has a higher willingness to pay. The authors provide process evidence that the effect of the buyer's identity on the seller's willingness to accept is driven by concerns about heritage loss. The findings contribute to literatures on sharing, sentimental goods, psychological ownership, and the endowment effect and have marketing implications for consumer goods (e.g., collectibles) that derive product value by connecting consumers to meaningful history and traditions.